Menyinergikan Aturan Prudensial Dan Aturan Kepatuhan Syariah Pada Perbankan Syariah Di Indonesia - Agus Triyanta (Jurnal Hukum IUS QUIA IUSTUM, 2019)
Besidesbeing  generally  bound  by  prudential  principles  in  banking  regulations,  Islamic  banking  in Indonesia is also bound by sharia principles. In reality, there are several contradictions between these two  jurisdictions  (conventional  banking  and  Islamic  banking).  This  article  aims  to  discuss  why  the contradictions between these two jurisdictions can occur. Furthermore, how the possibilities are to make harmony or adjustment among the various different elements, so that these two different jurisdictions can synergistically play a role in driving the development of Islamic banking in Indonesia. The research method in this article is normative legal research with a qualitative analysis model. The conclusion of this article showed that the set of regulations related to the prudential principle of banking in two banking models  (conventional  and  sharia)  in  fact  were  the  same.  It  was  because  this  regulation  related  to banking  prudential  was  originally  designed  for  conventional  banking,  and,  when  applied  to  Islamic banking, various adjustments were needed, for example in the collateral case. This article recommends that sharia-based prudential principles should be immediately integrated into the regulation of banking prudential principles in general to prevent any problems arose from the application of Islamic banking.